Antidiabetic Activity of Vinca rosea Extracts in Alloxan-Induced Diabetic Rats. (7th June 2010) - Ahmed, Mohammed Fazil; Kazim, Syed Mohammed; Ghori, Syed Safiullah; Mehjabeen, Syeda Sughra; Ahmed, Shaik Rasheed; Ali, Shaik Mehboob; Ibrahim, Mohammed
Abstract : The present study was carried out to evaluate the antidiabetic activity of Vinca rosea methanolic whole plant extracts in alloxan induced diabetic rats for 14 days. The methanolic whole plant extract at high dose (500 mg/kg) exhibited significant anti-hyperglycemic activity than whole plant extract at low dose (300 mg/kg) in diabetic rats. The methanolic extracts also showed improvement in parameters like body weight and lipid profile as well as regeneration ofβ -cells of pancreas in diabetic rats. Histopathological studies reinforce the healing of pancreas, by methanolic Vinca rosea extracts, as a possible mechanism of their antidiabetic activity.